Inside and outside views of the Croatian police - Prprović, Barbara (International journal of comparative and applied criminal justice, 2022)
This paper explores public views about police integrity and contrasts them with the police views about police integrity. It also compares citizen and police officer views about the police. A modified version of the police integrity survey, containing 14 hypothetical vignettes describing various forms of police misconduct, was distributed to both students and police officers in Croatia. The respondents in the study, 1,142 police officers from Croatia and 450 students from the University of Zagreb, shared their views of how serious most police officers would evaluate misconduct, the expected discipline, and whether they would report the described misconduct. The results suggest not only that students expressed less positive views of the police than police officers themselves did, but also that students expressed attitudes associated with somewhat lower integrity than police officers did.